PENGARUH MEKANISME GOOD CORPORATE GOVERNANCE TERHADAP MANAJEMEN LABA - Rida Ristiyana, 09.05.52.0133; Poerwati, Tjahjaning (Students Journal of Accounting and Banking, 2013)
Earnings management is one of the consequences of information asymmetry in agency theory, this is because the manager (agent) know more information about the company is managed. Earnings management actions result in financial statements that do not correspond to the real situation. Good Corporate Governance (GCG) Mechanism is expected to create a climate of good governance in control of earnings management practice. This study aims is find out and analyze the effect good corporate governance mechanisms are reviewed of the institutional ownership, the management ownership, the audit committee and the independent commissioner of earnings management. The research sample that fulfilled the criteria as many as 26 manufacturing companies listed on the Indonesia Stock Exchange during the period from 2009 to 2011. The sampling technique used was purposive sampling method, the number of data observations (n) = 78. The analytical tool used in this study is Multiple Linear Regression. Based on the results of the individual tests, show that GCG mechanism are reviewed of the institutional ownership, the management ownership and the independent commissioners is significant positive effect of earnings management. Meanwhile, good corporate governance mechanisms are reviewed of the audit committee show is insignificant negative effect of earnings management. Based on the results of the model tests, show that together is significant effect between good corporate governance mechanisms (the institutional ownership, the management ownership, the audit committee and the independent commissioners) of earnings management. Keywords: Institutional Ownership, Management Ownership, Audit Committee, Independent Commissioner and Earnings Management.